Caveolin 1 restricts Group A Streptococcus invasion of nonphagocytic host cells. (6th September 2017) - Lim, Jin Yan; Barnett, Timothy C.; Bastiani, Michele; McMahon, Kerrie‐Ann; Ferguson, Charles; Webb, Richard I.; Parton, Robert G.; Walker, Mark J.
Abstract: Caveolae are composed of 2 major proteins, caveolin 1 (CAV1) and cavin 1 or polymerase transcript release factor I (CAVIN1). Here, we demonstrate that CAV1 levels modulate invasion of Group A Streptococcus (GAS) into nonphagocytic mammalian cells. GAS showed enhanced internalisation into CAV1‐knockout mouse embryonic fibroblasts and CAV1 knockdown human epithelial HEp‐2 cells, whereas overexpression of CAV1 in HEp‐2 cells reduced GAS invasion. This effect was not dependent on the expression of the GAS fibronectin binding protein SfbI, which had previously been implicated in caveolae‐mediated uptake. Nor was this effect dependent on CAVIN1, as knockout of CAVIN1 in mouse embryonic fibroblasts resulted in reduced GAS internalisation. Although CAV1 restricted GAS invasion into host cells, we observed only minimal association of invading GAS (strain M1T1 5448 ) with CAV1 by immunofluorescence and very low association of invading M1T1 5448 with caveolae by transmission electron microscopy. These observations suggest that physical interaction with caveolae is not needed for CAV1 restriction of invading GAS. An indirect mechanism of action is also consistent with the finding that changing membrane fluidity reverses the increased invasion observed in CAV1‐null cells. Together, these results suggest that CAV1 protects host cells against GAS invasion by a caveola‐independent mechanism. Abstract : Caveolae are membrane organelles composed of two major proteins, caveolin‐1 (CAV1) and cavin‐1 (CAVIN1). This work demonstrates that CAV1 levels modulate the invasion of Group A Streptococcus (GAS) into non‐phagocytic mammalian cells. Knockdown of CAV1 (shCAV1) increases GAS invasion, while expression of CAV1 (YFP‐CAV1) reduces invasion. Physical interaction of invading GAS with caveolae was rarely detected by transmission electron microscopy, suggesting that CAV1 protects host cells against GAS invasion by a caveola‐independent mechanism.